NIGERIAN POLITICIANS AND LANGUAGE USE DURING POLITICAL COMPAIGNS: A STUDI OF SELECT SPEECHES - Inegbe, Miriam Stephen (UI Scholars Hub, 2024)
This essay appraised linguistic features in selected utterances of some prominent and leading Nigerian politicians during political rallies held between October and December, 2022. These utterances, which serve as data for this paper were extracted from some Nigerian tabloids like NaijaNews.com, Opera News, Politic.nigeria.com, RealMedia, Vanguard News, Voice of the People (VoP) and www.thisdaylive.com. In linguistics, utterances are viewed as unit of speech. The significant meaning of speech, therefore, embeds in the utterance which may provide a basis for social positions and further interpretative actions or decisions by the listener. The data for this study were eleven (11) purposively selected excerpts collected from some Nigerian media outfits. The selected data were appraised and analyzed from the linguistic perspective of John Langshaw Austin’s speech act theory, although other linguistic insights are gleaned from other speech act analytic scholars. The speech theory of John Langshaw Austin emphasizes on meaning embedded in an utterance. His speech act is interested in what the speaker’s or the writer’s intention is, and what he or she does with words but not necessarily the meaning of words within the utterance. The essay revealed that political rally utterances are purposeful utterances laced with vituperations, repetitions, and choice codes meant to persuade and manipulate the electorates against their perceived opponents. These social political attributes, negative in the manner of approach, present contemporary Nigerian politicians as desperados whose intentions are to grab political power by all means. Therefore, the essay recommends constructive criticism and politeness in political rally utterances when doing things with words in order to reduce and curb unnecessary political hatred, social battery, democratic mayhem, oppositional killings and anarchy caused by unethical political utterances.